Towards metamaterial rods with amplitude-dependent band gaps: A superelastic alloy-based approach. (1st March 2022) - Yang, Bin; Guo, Kai; Sun, Jie
Abstract: In this paper, a novel approach to designing metamaterial rods with amplitude-dependent band gaps is proposed. This feature is achieved with resonators that are designed to exploit the stress plateau in the stress–strain curve of the superelastic alloy used in the rods. The rods are fabricated with a single constituent material, i.e., a superelastic alloy, which facilitates monolithic fabrication through additive manufacturing and avoids the complex assembly process required in previous studies. Moreover, horseshoe lattices are introduced into the designed resonator spring, which increases the design flexibility; i.e., the characteristic values of the spring stiffness and the band gap can be easily regulated by adjusting the design variables of the horseshoe lattice. Extensive case studies validate the effectiveness of the proposed approach. Highlights: The metamaterial rod is fabricated with a single kind of constituent material. Stress plateau of the superelastic alloy ensures the amplitude-dependent band gap. Horseshoe lattices are introduced to increases the design flexibility.